STROKE OUTCOMES IN NON-DIABETIC, DENOVO DIABETIC AND DIABETIC INDIAN PATIENTS MEASURED BY MODIFIED RANKIN SCALE: AN OBSERVATIONAL STUDY - Ahmed, Syed Junaid; Masood, Abdur Rahman Mohd; Sumana, Safiya; Ghori, Khadeer Ahmed; Ansari, Javed Akhtar; Khan, Musa (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: Hyperglycemia is a known risk factor which adversely impacts the outcomes in stroke patients compared to patients with normal blood glucose levels. Patients suffering from an acute stroke who are previously nonhyperglycemic may show elevated blood glucose levels. The present study was designed to measure the outcomes in denovo diabetic and diabetic stroke patients compared to nondiabetics. Methods: A prospective observational study over a period of 6 mo, in which 103 patients were divided into three cohorts based on their blood glucose levels (nondiabetic, denovo diabetic and diabetics). The modified Rankin scale (mRS) score was calculated at in-hospital admission and discharge in these three cohorts. The initial and final scores were correlated and mean differences with respect to outcomes between all the three cohorts was calculated. Results: The mean mRS at the time of hospital admission in diabetics and nondiabetics was 3.6±0.81 and 3.3±0.78 which decreased to 2.8±0.95 and 2.9±0.83 respectively at the time of discharge. The mean mRS score in denovo diabetic stroke patients during in-hospital admission was 4±0.81 which was calculated as 3.7±0.85 at the time of discharge. The mean difference in mRS score in diabetics vs non-diabetics was found to be 0.73±0.8 (p =<0.001). The mean difference in mRS score of denovo diabetics vs non-diabetics and denovo diabetics vs diabetics was 0.30±0.63 and 0.38±0.61 respectively (p = 0.1). Conclusion: Results of these observational study in Indian patients, highlights the need for controlling hyperglycemia in stroke patients to improve outcomes and to prevent mortality arising out of acute stroke attacks.